Pengaruh Metode Bercerita Terhadap Kemampuan Berbicara Pada Anak Usia Dini Di TK Babunnajah - Ayi Kusjiwa (Metakognisi, 2021)
The purpose of this research is the effect of storytelling method on speaking ability in early childhood in Babunajah Kindergarten. This research was conducted to determine how storytelling method affects speaking ability in early childhood. This research is a quantitative research. The subjects of this study were all early childhood participants in Babunnajah Kindergarten. To obtain data in this study used research instruments consisting of two types, namely test and non-test. The type of test instrument is a test of understanding storytelling and a non-test instrument in the form of a speaking ability questionnaire in the influence of the storytelling method on speaking skills in early childhood in Babunnajah Kindergarten. Analysis of understanding data using instruments. The results of this study indicate that based on the results of the analysis of the significance of the regression coefficient with the t-test obtained: > 35.29 > 2.09, this is quantitative information to make the conclusion that: there is a significant effect of storytelling method on speaking ability of early childhood in Babunnajah Kindergarten.